Aime Moi Ou Deteste Moi (AMDM): a therapeutic photography overcome emotional abuse of differently-abled students in Malaysia / Juaini Jamaludin and Hasniza Hassim - Jamaludin, Juaini; Hassim, Hasniza (Universiti Teknologi MARA, Kedah, 2018)
Emotional abuse, one of the most common and least understood of the four types of abuse, is strongly related to disability. People with disabilities are reported to experience rates of abuse at a significantly higher rate than non-disabled people. At the same time, numerous disabilities appear to be highly correlated with abuse, suggesting that there may be a relationship between emotional abuse and disability that should be further explored. Independent of one another, having a disability and experiencing emotional abuse can have profound effects and enduring consequences on individuals and their families. Phototherapy involves the use of photos as visual aid to solve an individual emotional abuse. Photography is a therapeutic tool which can be used by the professional librarians / Library Media Teacher usually with cooperation with counsellors and psychologist. This project AMDM bringing up the cooperation between academician from the Faculty of Information Management and Faculty of Art & Design, UiTM Kedah with the Library Media leacher from the Special Education Schools in the state of Kedah.